Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Erza
a) \(\frac{3}{5}-\frac{1}{3}-\frac{1}{6}=\frac{18}{30}-\frac{10}{30}-\frac{5}{30}=\frac{18-10-5}{30}=\frac{1}{10}\)
b) \(\frac{4}{7}\times\frac{5}{8}\times\frac{7}{12}=\frac{4\times5\times7}{7\times8\times12}=\frac{140}{672}=\frac{5}{24}\)
c) \(\frac{25}{28}\div\frac{15}{14}\times\frac{6}{7}=\frac{25}{28}\times\frac{14}{15}\times\frac{6}{7}=\frac{25\times14\times6}{28\times15\times7}=\frac{2100}{2940}=\frac{5}{7}\)
Thấy đúg thì tk nha các bn !!
a,3/5 - 1/3 - 1/6
= 4/9 - 1/6
= 5/9
b,4/7x5/8x7/12
= 5/14 x 7/12
= 5/24
c,25/18 :15/14 x 6/7
= 25/28 x 14/15 x 6/7
= 5/6 x 6/7
= 5/7
\(D=\frac{1}{10}+\frac{1}{15}+\frac{1}{21}+\frac{1}{28}+\frac{1}{36}+\frac{1}{45}\)
\(D=\frac{2}{20}+\frac{2}{30}+\frac{2}{42}+\frac{2}{56}+\frac{2}{72}+\frac{2}{90}\)
\(D=\frac{2}{4.5}+\frac{2}{5.6}+\frac{2}{6.7}+\frac{2}{7.8}+\frac{2}{8.9}+\frac{2}{9.10}\)
\(D=2\left(\frac{1}{4}-\frac{1}{5}+\frac{1}{5}-\frac{1}{6}+\frac{1}{6}-\frac{1}{7}+...+\frac{1}{9}-\frac{1}{10}\right)\)
\(D=2\left(\frac{1}{4}-\frac{1}{10}\right)=2\cdot\frac{3}{20}=\frac{3}{10}\)
\(E=\frac{10}{56}+\frac{10}{140}+\frac{10}{260}+...+\frac{10}{1400}\)
\(E=\frac{5}{28}+\frac{1}{14}+\frac{1}{26}+...+\frac{1}{140}\)
\(E=\frac{5}{28}+\frac{5}{70}+\frac{5}{130}+...+\frac{5}{700}\)
\(E=\frac{5}{4.7}+\frac{5}{7.10}+\frac{5}{10.13}+...+\frac{5}{25.28}\)
\(E=\frac{5}{3}\cdot\left(\frac{1}{4}-\frac{1}{7}+\frac{1}{7}-\frac{1}{10}+...+\frac{1}{25}-\frac{1}{28}\right)\)
\(E=\frac{5}{3}\cdot\left(\frac{1}{4}-\frac{1}{28}\right)=\frac{5}{3}\cdot\frac{3}{14}=\frac{5}{14}\)
Câu b:
\(\frac{21}{8}:\frac{5}{6}+\frac{1}{2}:\frac{5}{6}\)
= \(\frac{63}{20}+\frac{3}{5}\)
= \(\frac{15}{4}\)
\(\left(\frac{21}{8}+\frac{1}{2}\right):\frac{5}{6}\)
\(\frac{25}{8}:\frac{5}{6}\)
\(\frac{25}{8}.\frac{6}{5}\)
\(\frac{30}{8}\)
\(\left(a\right)\frac{34-x}{30}=\frac{5}{6}\)
\(\frac{34-x}{30}=\frac{25}{30}\)
34 - x = 25
x = 34 - 25 = 9
\(\left(b\right)\frac{x+13}{34}=\frac{12}{17}\)
\(\frac{x+13}{34}=\frac{24}{34}\)
x + 13 = 24
x = 24 - 13 = 11
\(\left(c\right)\left(x+\frac{1}{3}\right)+\left(x+\frac{1}{9}\right)+\left(x+\frac{1}{27}\right)+\left(x+\frac{1}{81}\right)=\frac{56}{81}\)
\(4x+\frac{1}{3}+\frac{1}{9}+\frac{1}{27}+\frac{1}{81}=\frac{56}{81}\)
Đặt \(A=\frac{1}{3}+\frac{1}{9}+\frac{1}{27}+\frac{1}{81}\)
Ta có : \(3A=1+\frac{1}{3}+\frac{1}{9}+\frac{1}{27}\)
\(3A-A=1+\frac{1}{3}+\frac{1}{9}+\frac{1}{27}-\frac{1}{3}-\frac{1}{9}-\frac{1}{27}-\frac{1}{81}\)
\(2A=1-\frac{1}{81}=\frac{80}{81}\)
\(A=\frac{80}{81}\div2=\frac{40}{81}\)
\(\Rightarrow4x+\frac{40}{81}=\frac{56}{81}\)
\(4x=\frac{56}{81}-\frac{40}{81}\)
\(4x=\frac{16}{81}\)
\(x=\frac{16}{81}\div4=\frac{4}{81}\)
a,
\(x+\frac{7}{15}=1\frac{1}{20}\)
\(x+\frac{7}{15}=\frac{21}{20}\)
\(x=\frac{21}{20}-\frac{7}{15}=\frac{63}{60}-\frac{28}{60}\)
\(x=\frac{35}{60}=\frac{7}{12}\)
b,
\(\left[3\frac{1}{2}-x\right]\cdot1\frac{1}{4}=\frac{15}{16}\)
\(\left[\frac{7}{2}-x\right]\cdot\frac{5}{4}=\frac{15}{16}\)
\(\frac{7}{2}-x=\frac{15}{16}:\frac{5}{4}=\frac{3}{4}\)
\(\frac{7}{2}-x=\frac{3}{4}\Rightarrow x=\frac{7}{2}-\frac{3}{4}\)
\(x=\frac{11}{4}\)
c,
\(1\frac{1}{5}x+\frac{2}{3}x=\frac{56}{125}\Leftrightarrow\frac{6}{5}x+\frac{2}{3}x=\frac{56}{125}\)
\(\frac{28}{15}x=\frac{56}{125}\Rightarrow x=\frac{6}{25}\)
d,
\(60\%x+0,4x+x:3=2\)
\(\frac{3}{5}x+\frac{2}{5}x+\frac{1}{3}x=2\)
\(\frac{4}{3}x=2\Rightarrow x=\frac{3}{2}\)
Nguyễn Anh Thiện
a)
x + \(\frac{7}{15}\) = \(1\frac{1}{20}\)
X + \(\frac{7}{15}=\frac{21}{20}\)
X \(=\frac{21}{20}-\frac{7}{15}\)
X \(=\frac{63}{60}-\frac{28}{60}=\frac{35}{60}=\frac{7}{12}\)
^^ Học tốt !
Đặt: \(A=\frac{1}{14}+\frac{1}{28}+\frac{1}{56}+....+\frac{1}{896}\)
\(\Rightarrow\)\(2A=\frac{1}{7}+\frac{1}{14}+\frac{1}{28}+....+\frac{1}{448}\)
\(\Rightarrow\)\(2A-A=\left(\frac{1}{7}+\frac{1}{14}+....+\frac{1}{448}\right)-\left(\frac{1}{14}+\frac{1}{28}+.....+\frac{1}{896}\right)\)
\(\Rightarrow\)\(A=\frac{1}{7}-\frac{1}{896}=\frac{127}{896}\)
mà \(A=x-3\)
nên \(x-3=\frac{127}{896}\)
\(\Rightarrow\)\(x=3\frac{127}{896}\)
mink cần gấp